Plicatin C: A New Cinnamate Derivative from Mangrove-derived Fungus Aspergillus terreus DM62 - Tian, Danmei; Chen, Mei; Ding, Wenjuan; Li, Jia; Wu, Shi; Hong, Kui; Tang, Jinshan (Natural Products Journal, The, 2024)
Background: Marine fungi have been proven to be a new arsenal for the discovery of valuable secondary metabolites. Method: Fungus strain Aspergillus terreus DM62 was initially fermentated using solid corn medium and PDA liquid medium. Subsequently, extensive chromatographic methods were applied to isolate the fermentation cultures of DM62, and the chemical structures of isolate compounds were elucidated by pectroscopic analyses and optical rotations comparison. Additionally, α-glucosidase and ATPcitrate lyase (ACL) inhibitory activities of isolate compounds were assessed to investigate their hypoglycemic and lipid-lowering activities. Result: A new cinnamate derivative, plicati n C (1), together with 18 known compounds, were isolated from the solid and liquid state fermentations of A. terreus DM62. Activity evaluation showed that compounds 3, 6, and 8-10 exhibited stronger α-glucosidase inhibitory activities than acarbose at 400 μM, and butenolide 3, with an IC50 value of 21.5 μM, was discovered with significant ACL inhibitory activity for the first time. Conclusion: This study not only discovered a new cinnamate derivative but also found butenolides with potent ACL inhibitory activity, which is favorable to clarify their pharmacological mechanism in the treatment of metabolic disease.
Keywords: diphenyl ether